Agroforestry as Climate Change Adaptation The Case of Cocoa Farming in Ghana - Olwig, Mette Fog; Skovmand Bosselmann, Aske; Owusu, Kwadwo (Springer Nature, 2024)
This open access book provides multidisciplinary perspectives on the potential of agroforestry to mitigate the negative impacts of climate change on cocoa production. Against the backdrop of increasingly precarious farmer livelihoods, it focuses on cocoa-agroforestry in Ghana - the second largest producer of cocoa in the world. Taking the reader on a journey across experimental plots and on-farm studies, the book delivers a holistic understanding of cocoa-agroforestry. Chapters examine historical yield and climate interactions, the effects of heat and drought on cocoa plants and the role of differing shade trees on soil fertility, yields, pests and diseases. The book discusses the socioeconomics of shade tree management, including cost-benefits, tree rights and competition for natural resources emphasizing policy implications and recommendations. Taking a multidisciplinary approach to climate-agriculture interactions, the book provides an innovative understanding of agroforestry and perennial cropping systems that goes beyond the Ghanaian cocoa belt. It is of relevance to students, researchers, farmers, practitioners and policymakers working with agroforestry and climate change adaptation. This is an open access book.